2012
DOI: 10.1002/ptr.4712
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Hair Growth by Rosmarinus officinalis Leaf Extract

Abstract: Topical administration of Rosmarinus officinalis leaf extract (RO-ext, 2 mg/day/mouse) improved hair regrowth in C57BL/6NCrSlc mice that experienced hair regrowth interruption induced by testosterone treatment. In addition, RO-ext promoted hair growth in C3H/He mice that had their dorsal areas shaved. To investigate the antiandrogenic activity mechanism of RO-ext, we focused on inhibition of testosterone 5α-reductase, which is well recognized as one of the most effective strategies for the treatment of androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 27 publications
1
42
0
4
Order By: Relevance
“…It has antiandrogenic effect and hair growth-promoting activity apart from antioxidative, anti-inflammatory, antibacterial, and antitumor effects [43]. In CAM, R. officinalis is often used in aromatherapy to treat anxiety-related conditions and increase alertness, although it has occasionally been used to stimulate hair growth [41].…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
See 2 more Smart Citations
“…It has antiandrogenic effect and hair growth-promoting activity apart from antioxidative, anti-inflammatory, antibacterial, and antitumor effects [43]. In CAM, R. officinalis is often used in aromatherapy to treat anxiety-related conditions and increase alertness, although it has occasionally been used to stimulate hair growth [41].…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
“…They also showed significant promotion of hair growth after 16 days of topical administration. Among the some constituents of R. officinalis [i.e., rosmarinic acid, ursolic acid, 12-methoxycarnosic acid (12-MCA)], it was demonstrated that inhibitory activity of 12-MCA on 5α-reductase was higher than rosmarinic acid and ursalic acid (82.4, 14.2, and 2.5% inhibition at 200 μg/ml, respectively) [43].…”
Section: Rosmarinus Officinalismentioning
confidence: 99%
See 1 more Smart Citation
“…Topical administration of R . officinalis leaf extract also showed inhibitory activity of 82.4% and 94.6% at 200 and 500 µg/mL, respectively, against 5αR [24].…”
Section: Plant Raw Materialsmentioning
confidence: 99%
“…Some 5αR inhibitors from natural products have been discovered by our group, i.e., 12-methoxycarnosic acid in Rosmarinus officinalis leaf,[19] ginsenoside Ro in the rhizome of red ginseng,[20] kaikasaponin and soyasaponin in flowers of Pueraria thomsonii [21] and fatty acids and ethinylestradiol in spores of Lygodium japonicum . [22]…”
Section: Introductionmentioning
confidence: 99%